Ablation of NK1 receptor bearing neurons in the nucleus of the solitary tract blunts cardiovascular reflexes in awake rats - Abdala, Ana Paula L.; Schoorlemmer, Guus H. M.; Colombari, Eduardo [UNESP] (Elsevier B.V., 2006)
The nucleus of the solitary tract (NTS) receives primary afferents involved in cardiovascular regulation. We investigated the role of NK1-receptor bearing neurons in the NTS on cardiovascular reflexes in awake rats fitted with chronic venous and arterial cannulae. These neurons were lesioned selectively with saporin conjugated with substance P (SP-SAP, 2 mu M, bilateral injections of 20 nL in the subpostremal NTS, or 200 nL in both the subpostremal and the commissural NTS). Before, and 7 and 14 days after injection of SP-SAP, we measured changes in blood pressure and heart rate induced by i.v. injection of phenylephrine and nitroprusside (baroreceptor reflex), cyanide (arterial chemoreceptor reflex), and phenylbiguanide (Bezold-Jarisch reflex). The smaller injections with SP-SAP completely abolished NK1 receptor staining in the subpostremal NTS. The larger injections abolished NK1 receptor immunoreactivity in an area that extended from the commissural NTS to the rostral end of the subpostremal NTS. The lesions seemed to affect only a limited number of neurons, since neutral red stained sections did not show any obvious reduction in cell number. The smaller lesions reduced the gain of baroreflex bradycardia and the hypotension induced by phenylbiguanide. The larger lesions completely abolished the response to phenylbiguanide, blocked the baroreflex bradycardia induced by phenylephrine, severely blunted the baroreflex tachycardia, and blocked the bradycardia and reduced the hypertension induced by cyanide. Thus, these responses depend critically on NK1-receptor bearing neurons in the NTS. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: tachykinin; baroreflex; chemoreflex; Bezold-Jarisch reflex; nucleus of the solitary tract; substance P